Energy expenditure and fatigue - Kneffel, S. (International Canoe Federation, 2020)
The video is part of "ICF performance education" - a free online series aimed at coaches, athletes and administrators who wish to expand their knowledge on specific topics to improve their own performance or that of their athletes. Experts from around the world host these sessions online, with the opportunity for the attendees to ask questions which will be answered live at the end of the webinar. The videos are posted online afterwards for those who are unable to attend at the specified day and time.